HUBUNGAN MUTU PELAYANAN KEPERAWATAN DENGAN TINGKAT KEPUASAN PASIEN (Studi di RSU Dr. Wahidin Sudiro Husodo Mojokerto Tahun 2014) - Angga Zainudin; Hindyah Ike; Nurul Huda (Jurnal Keperawatan, 2014)
The lack of quality of nursing care, the nurse do not perform minimum service standard in the set, So thatpatient feel the service provided is not in accordance with costs incurred and the results received service.Minimum service standard in Indonesian hospital in 2013 based on the results of a survey of communitysatisfaction index of 81% of the people are very are satisfied. Standard care hospital in the province of EastJava based community satisfaction index by 86% are satisfied (RI Department of Health, 2013). Meanwhile,in Hospital Dr Wahidin Sudiro Husodo Mojokerto patient satisfaction rate of 75% (Medical Care, 2013).This study aimed analyzing the relationship the quality of nursing care with patient satisfaction studies inHospital Dr. Wahidin Sudiro Husodo Mojokerto.This study used a cross sectional analytic design with a sample population of 219 patients and 44 patientstotaled probability sampling is done by simple random sampling approach. Data processing with editing,coding, scoring, tabulating and software SPSS version 16.0 statistical test "Spearman Rank's" by rate  =0.000 <0.05.Based on the results of the study showed the majority of the quality of nursing care is less category, showedthat more than half of the respondents level of patient satisfaction was less are satisfied. Results of statisticaltest Spearman Rank's ( = 0.000 <0.05) so that H1 is accepted to mean there is a relationship between thequality of nursing care with patient satisfaction.From the results of this study are expected to improve the skills of nurses and skills when examining patients.for services provided by nurses patients were satisfied with the services provided.Key words: Quality of nursing care, patients satisfaction rate